Microbial Community Dynamics within Frost Boils of Browning Peninsula, Antarctica - Pusasaini, Sarita (UNSW Sydney, 2014)
Browning Peninsula is a barren and ice free landscape in the Windmill Island, Eastern Antarctica which has experienced very little human activity. It is located in low valley consisting of large number of frost boils approximately 2-10 m in diameter, combined with an active layer of about 30 cm. Our aim was to investigate the microbial diversity of this unique, pristine environment. For this study, 18 soils were collected across 3 parallel transects using a spatially explicit sampling design. Soil genomic DNA was extracted and 454 pyrotag sequencing along with qPCR was performed targeting the bacterial 16S rRNA and fungal ITS/18S rRNA genes. Both the microbial and environmental data were analysed using Primer 6 and Permanova software and the community diversity and their similarity was investigated. Our results showed the bacterial community to consist predominantly of Actinobacteria (up to 55%), Chloroflexi (≥ 10%), Acidobacteria, Cyanobacteria, Proteobacteria and Gemmatimonadetes. While Ascomycota (≥ 96%), Basidiomycota (> 1.5%) and Fungi incertae sedis (< 1%) were the dominant fungi. A significant relationship between microbial community structures and environmental properties (extrinsic and intrinsic) was observed. For bacterial communities elevation, sand, conductivity, Cl-, SO4-- and total nitrogen were driving community pattern, while mud, total nitrogen, total carbon, SiO2 and sodium oxide were affecting fungal community distributions. Bacterial communities from samples of same polygon were more similar than the communities from different polygons and distance. While Fungal community distributions were random (soil sample specific) ie no trend was observed over the landscape or individual polygons. In this study, a culture clash was observed between the culture dependent and independent approaches to microbial characterisation. The artificial media recovered 4 (Pedobacter, Aminobacter, Dyella, Shingopyxix) bacterial genera and 3 (Engyodontium, Peniopora, Phoma) fungal genera which neither present in SSMS nor in soil based 454 pyrosequencing data. Comprehensive analysis of interboil variation may uncover what was happening in these boils. In the future it is required to have polygon specific sampling across different positions (edge, center), various depths of individual polygon and use of illumina pyrotaq sequencing platform to understand the ecosystem within these polygons with greater microbial dataset coverage.